PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR DALAM TEMA “DUA UDARA BERSIH BAGI KESEHATAN” KELAS V MI NW AIKMEL - Muh. Hifni (Al-mujahidah, 2020)
considering to observations done at MI NW Aikmel of the V graders in thematic lessons, the results show that the use of learning model used by the teacher is only using the conventional learning model. The teacher's role is only as a center or controller in the learning process (teacher centered). The learning given by the teacher is giving lectures to explain the material, and then giving assignments to students according to the handbook. The method used is a quantitative method with experimental design. Based on the discussion of the data analysis that that Problem Based Learning (PBL) model of learning outcomes in grade V on Clean Air for Health at MI NW Aikmel in Academic Year of 2019/2020. This is in accordance with the t-test results obtained, namely t count of 10.514 and t table of 1.729 with a significant level of 5%, so that there is t count> t table (10.514> 1.729), then Ha is accepted and Ho is rejected. This means that there is the effect of the Problem Based Learning (PBL) learning model on student learning outcomes on the theme of clean air for health in grade V of MI NW Aikmel in the academic year of 2019/2020